Comparative numerical analysis of different strengthening systems of historical brick arches - Zielińska, Monika (Zielona Góra: Uniwersytet Zielonogórski)
The article presents a comparative numerical analysis of various ways to strengthen historical brick arches. Five ways of strengthening brick arches with steel tie-rods have been proposed. Two of these involve the use of braces wrapped around pillars supporting the arch connected with a tie-rod; the other two ways involve the use of the tie-rods with welded metal sheets of different sizes; the latter involves the use of a tie-rod glued with the use of an epoxy adhesive.
Keywords: historical building; brick arches; tie-rod; modal analysis; FEM